Animal-derived foods: consumption, composition and effects on health and the environment: an overview - Wood, J. D.; Giromini, C.; Givens, D. I. (Frontiers in Animal Science, 2024)
Consumption of animal-derived foods (ADFs), particularly red meat, is declining in high-income countries because of concerns over health and the effects on climate change but is increasing in low-and middle-income countries. As a group of foods, ADFs are high in good-quality protein and several key vitamins and minerals (notably vitamin B12, iron and zinc). There is evidence, though, that processed red meat poses risks of cardiovascular disease (CVD) and colorectal cancer and the same risks, although not so strong, are apparent for unprocessed red meat. Milk and milk products generally have a neutral disease risk and there is evidence of reduced risks of CVD and colorectal cancer. Similarly, white meat (chicken and fish) is not associated with disease risk whilst eggs have been linked with increased CVD risk because of their cholesterol content. The risks of chronic disease seem higher in highincome than in low-and middle-income countries, possibly due to different levels of consumption. Production of ADFs results in high greenhouse gas emissions per unit of output compared with plant proteins. Ruminant meat production has particularly high costs but wide variation between farms in different regions of the world suggests costs can be significantly lowered by changes to production systems. Reducing ADF consumption to benefit health and the environment has been proposed but in low-income countries, current levels of consumption of ADFs may be compatible with health and climate targets.Animal-derived foods (ADFs) (meat and meat products, milk and milk products, fish and seafood, and eggs) have been important constituents of the